Existenzgründungsförderung in Deutschland: Zwischenergebnisse aus der Hartz-Evaluation - Marco Caliendo; Alexander Kritikos; Frank Wießner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– The promotion of business start-ups by formerly unemployed individuals has become an increasingly important instrument of German active labour market policy (ALMP) in recent years. With the introduction of the start-up subsidy (Existenzgründungszuschuss) on 1.1.2003 unemployed individuals who wish to set up their own business have now two instruments at their disposal - the first one being the bridging allowance (Überbrückungsgeld). In 2004 more than 350,000 people utilized either one of the two programmes, underpinning their importance within the set of ALMP instruments. In the context of the Hartz evaluation, we are assessing the two programmes with respect to their outreach and effectiveness. Our results show that both schemes help participants to avoid a return into unemployment. While this outcome is based on a sufficiently long observation period for the bridging allowance, results are still preliminary for the start-up subsidy. We further observe that the new programme attracts target groups which were previously underrepresented in the self-employment population. Accordingly start-ups which are supported by the bridging allowance differ considerably from those supported by the start-up subsidy.
Keywords: 330; Unternehmensgründung - Förderung; arbeitsmarktpolitische Maßnahme - Erfolgskontrolle; Überbrückungsgeld; Existenzgründungszuschuss; Hartz-Reform; Arbeitslosigkeitsbekämpfung; Unternehmenserfolg; Beschäftigungseffekte; Westdeutschland; Ostdeutschland; Bundesrepublik Deutschland